PERAN WANITA PEKERJA USAHA KULINER KHAS MINANGKABAU DALAM PENDIDIKAN EKONOMI KELUARGA - Yuhendri Leo V, M.Pd (FKIP Unswagati, 2022)
AbstractFemale workers in a family have two role as breadwinners and provide education to children. One of the education that they should teach children is economic education. This study aims 1) to describe the role of female workers of Minangkabau culinary businesses in family economic education, and 2) describe the way family economic education is carried out by female workers of Minangkabau culinary businesses to shape children's economic behavior. This research uses a qualitative approach with this type of phenomenological research. Data collection techniques are conducted with in-depth interviews, participation observations, and documentation. The research informant is female workers of Minangkabau culinary business in Tanah Datar Regency, West Sumatra Province. Data analysis technique uses the process of qualitative research data analysis Miles, Huberman, & Saldana consisting of four activities namely (1) data collection, (2) data condensation, (3) data display, and (4) conclusion: drawing and verifyng. The results showed that 1) female workers of Minangkabau culinary businesses play a role in family economic education as the first person to provide economic education to children, and 2) female workers of Minangkabau culinary businesses do family economic education by telling stories to children, habituation, and exemplaryness. The results of this study can be used as guidelines in conducting family economic education to shape children's economic behavior.Keywords: family economic education, Minangkabau culinary business, female worker, economic behavior.